Methodology for spatially resolved transient convection processes using infrared thermography. Issue 3 (16th April 2021) - Ikhlaq, Muhammad; Al-Abdeli, Yasir M.; Khiadani, Mehdi
ABSTRACT: Studies have previously looked at the transport processes in convection but there is a lack of detail on methods to characterize transient heat transfer behavior. An infrared methodology to spatially and temporally resolve transient heat transfer is presented and tested on turbulent impinging (cooling) jets (non-swirling, swirling, Re = 11, 600 to 35, 000, S = 0 to 1.05). The intricacies of data filtration and spatial discretization, as well as the structure of the image processing code are reported and a parametric study of factors influencing the time to reach steady-state is done. Results show that variations in jet behavior are manifest in the time to reach steady-state and can be resolved even in the first few seconds.